Evaluation of wind hazard over Sabah And Sarawak - Fiona, Gasing (2015)
Wind induce has become expressively reported widely in Malaysia. Numeral of study was conducted to mitigate and reduce wind risk in Malaysia. However most of the studies were conducted focusing to Peninsular Malaysia. There are very minimum information related to the wind characteristic in Sabah and Sarawak. Therefore this study was conducted to examined and evaluate the potential of wind risk in Sabah and Sarawak. Meteorological Data from meteorological station are used in directive to evaluate the wind storm risk in Sabah and Sarawak. Geographical Information System is used to evaluate the wind speed over Sabah and Sarawak. From the wind speed map produced, it shows those wind speed tendencies are periodically repeated anually for both state. The monsoon wind devided into two seasonal which called southwest monsoon between May to September and northeast between November to Mac. Frequent strong wind was observed during the southwest monsoon. This result shows opposite characteristic compare to the Peninsular Malaysia where the higher wind speed recorded during the Northeast Monsoon. This study also identify that damage occured in Sabah are significantly related to the monsoon season where numbers of damage is highly reported during this period. However in Sarawak there are lower significant relationship between the damage occured and the monsoon season. The damage were reported highly during the inter change of the monsoon season. During the inter change monsoon localised thunderstorm were frequently occured. Therefore the wind induce damage in Sarawak are significantly due to the micro scale event rather than seasonal monsoon wind. From all the result obtain, it can be conclude that wind characteristic is differs from place to place. Consequently, the wind risk is influenced by the geographical position at the specific location. Furthermore all consideration due to wind mitigation used in Peninsular Malaysia cannot simply consider in Sabah and Sarawak